Gradient‐Distributed Nucleation Seeds on Conductive Host for a Dendrite‐Free and High‐Rate Lithium Metal Anode. Issue 45 (17th September 2019) - Nan, Yang; Li, Songmei; Shi, Yongzheng; Yang, Shubin; Li, Bin
Abstract: Much attention is paid to metal lithium as a hopeful negative material for reversible batteries with a high specific capacity. Although applying 3D hosts can relieve the dendrite growth to some extent, gradient‐distributed lithium ion in 3D uniform hosts still induces uncontrolled lithium dendrites growth, especially at high lithium capacity and high current density. Herein, a 3D conductive carbon nanofiber framework with gradient‐distributed ZnO particles as nucleation seeds (G‐CNF) to regulate lithium deposition is proposed. Based on such a unique structure, the G‐CNF electrode exhibits a high average Coulombic efficiency (CE) of 98.1% for 700 cycles at 0.5 mA cm −2 . Even at 5 mA cm −2, the G‐CNF electrode performs a stable cycling process and high CE of 96.0% for over 200 cycles. When the lithium‐deposited G‐CNF (G‐CNF‐Li) anode is applied in a full cell with a commercial LiFePO4 cathode, it exhibits a stable capacity of 115 mAh g −1 and high retention of 95.7% after 300 cycles. Through inducing the gradient‐distributed nucleation seeds to counter the existing Li‐ion concentration polarization, a uniform and stable lithium deposition process in the 3D host is achieved even under the condition of high current density. Abstract : A 3D carbon nanofiber framework with gradient‐distributed ZnO particles is proposed for a dendrite‐free and high‐rate lithium metal anode. By introducing ZnO particles as lithium nucleation seeds to reduce the lithium nucleation energy and address the Li‐ion concentrate gradient in the 3D host, a uniform and safe lithium deposition process is achieved.